2015
DOI: 10.1590/s1517-838246220131141
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and safe handling of enteral diets in a hospital in Minas Gerais, Brazil

Abstract: Contamination of enteral diets represents a high risk of compromising the patient's medical condition. To assess the microbiological quality and aseptic conditions in the preparation and administration of handmade and industrialized enteral diets offered in a hospital in the Valley of Jequitinhonha, MG, Brazil, we performed a microbiological analysis of 50 samples of diets and 27 samples of surfaces, utensils, and water used in the preparation of the diets. In addition, we assessed the good handling practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 13 publications
1
24
0
2
Order By: Relevance
“…Three studies out of the eleven studies included were conducted in Iran [ 20 , 29 , 34 ] and two in the USA [ 25 , 28 ] ( Table 2 ). In addition, two other studies were conducted in Brazil [ 36 , 38 ], and one study each in Costa Rica [ 33 ], the Philippines [ 37 ], Saudi Arabia [ 35 ] and the UK [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies out of the eleven studies included were conducted in Iran [ 20 , 29 , 34 ] and two in the USA [ 25 , 28 ] ( Table 2 ). In addition, two other studies were conducted in Brazil [ 36 , 38 ], and one study each in Costa Rica [ 33 ], the Philippines [ 37 ], Saudi Arabia [ 35 ] and the UK [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Pinto et al [ 36 ], the two types of enteral feeds showed contamination by coliforms and Pseudomonas spp. although there was no positive sample for Staphylococcus aureus and Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Hospital kitchen appears to be a source of food contamination and occurrence of foodborne outbreaks in hospitalized patients in different countries (16)(17)(18)(19). Utensils, such as industrial blender and meat grinder, regardless of the contamination of raw food materials, could be the sources of pathogenic bacteria, because their cleaning and disinfection cannot accompany completely due to their designed structure (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, pH may influence the growth of pathogenic microorganisms and their deterioration in handmade enteral diets (Silvia et al, 2007). Rates close to neutrality (6.5 to 7.5) are more favorable for the growth of most of them (Von Atzingen et al, 2007;Pinto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Its analysis is important to assess the physiological acceptance capability of the diet and to avoid complications (Barrett et al, 2009 by providing a solubility environment to the nutrients. It is also crucial for the microbiological control of the solution (Klang et al, 2013;Pinto et al, 2015). Non-industrialized enteral diets with a pH rate favorable to microbiological growth may be an infection vector for patients undergoing enteral nutritional therapy if preventive hygiene measures are not applied during food handling (Blumenstein et al, 2014).…”
Section: Introductionmentioning
confidence: 99%